Analisa Kinerja Simpang Tak Bersinyal Akibat Hambatan Samping (Studi Kasus: Simpang Tiga Tak Bersinyal Jalan Kyai H. Asyari - Jalan Raya Boja Kaliwungu) - editor1; wawarisa; Distira Andy Liawan; Muhammad Nur Shoffa (JERA : Journal of Engineering Research and Application, 2022)
To analyze the performance of the intersection using the PKJI (2014) method, the data used in this research is primary data in the form of geometric intersections, traffic flow conditions, environmental conditions and side friction. Secondary data in the form of population growth data. Traffic data collection is carried out on Sundays, Mondays, and Fridays in the morning 06:00-08:00, Afternoon at 11:00-13:00, Afternoon at 15:30-17:30. The results showed that the highest number of SF during peak hours occurred at 16:30-17:30 WIB, namely as many as 711 events/hour on Sunday, 634.90 events/hour on Monday, and 735 events/hour on Friday. The performance of the intersection decreased due to the presence of side friction, seen the highest degree of saturation value of DS = 1,282, Capacity C = 2786.96 cur/hour, Delay D = 89.46 seconds/skr (service level F), Queue Opportunity QP = 67.64-139 ,64 %, and Side Friction SF = 711 events/hour. Based on the results of linear regression analysis, the effect of side friction on the degree of saturation is 60% with the equation Y = 0.0011X + 0.3938. An alternative solution to dealing with problems at intersections is the installation of APILL (Traffic Signaling Tool), because after an analysis has been carried out by widening the minor road and main road approaches, installing the median, and controlling road users, it shows the degree of saturation value from DS = 1,282 to DS =1.141 is still not in accordance with the target, namely DS = 0.85. From the alternative solutions that have been carried out, it cannot reduce the degree of saturation to DS = 0.85.Keywords: intersection performance, degree of saturation, delay, PKJI (2014), side friction.